Effectors of income-child health gradient: Role of dietary diversity on child nutritional status in selected slums of Dhaka city (Journal of Bangladesh Academy of Sciences, 2021)
Child dietary diversity (CDD) is an important nutritional outcome measuring the economic ability of a household to access a variety of foods during a determined period. Relating household income to CDD and child anthropometric failure, a cross-sectional study was conducted among 275 selected Dhaka city slum children of 6-12 years. Prevalence of stunting (18%), wasting (19.4%), and underweight (22%) among them were found similar to the current national figure. However, a sizable number of households showed increased DDS (>5), thereby indicating an increased household purchasing power (PP). Bivariate regression analysis showed that children from lower family income (≤6000 BDT) were 3 times more likely to be stunted as compared to children with greater family income [Unadjusted OR=3.097, 95% CI (1.578-6.077), p=0.001]. Furthermore, logistic regression showed that children who had